The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s13753-012-0019-x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of indigenous knowledge and disaster risk reduction: A case study from Baie Martelli, Pentecost Island, Vanuatu

Abstract: Despite reaching heights of >6 m and destroying a sizeable coastal settlement at the head of Baie Martelli (Pentecost Island, Vanuatu, South Pacific), the 26 November 1999 tsunamis caused only five fatalities from a threatened population of about 300 persons, most of whom fled inland and upslope before the waves struck. This remarkable survival rate is attributed to both indigenous knowledge, largely in the form of kastom knowledge, and information obtained from a video about tsunamis that was shown in the are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 30 publications
1
60
0
1
Order By: Relevance
“…Although no suggestion was made during our survey that any traditionally acquired information about environmental hazards, typically communicated orally, was not free for any member of the community to share with any other (typically parent to child), this is the case elsewhere in the Pacific and has been identified as a risk in future disaster response (Walshe and Nunn 2012). However, the same liberty does not apply in our sample villages to other forms of communication, such as songs and dances, some of which die with their composers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no suggestion was made during our survey that any traditionally acquired information about environmental hazards, typically communicated orally, was not free for any member of the community to share with any other (typically parent to child), this is the case elsewhere in the Pacific and has been identified as a risk in future disaster response (Walshe and Nunn 2012). However, the same liberty does not apply in our sample villages to other forms of communication, such as songs and dances, some of which die with their composers.…”
Section: Discussionmentioning
confidence: 99%
“…A study of tsunami awareness among communities in southern Pentecost Island in Vanuatu concluded that, despite government attempts to raise awareness, traditional knowledge about tsunami precursors and response was far more widespread, and accounted for the low number of fatalities during the 1999 tsunami (Walshe and Nunn 2012). A parallel situation was documented for tsunami response within indigenous coastal communities in Indonesia and Solomon Islands (McAdoo et al 2006, Fritz andKalligeris 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, isolation and small population size are suggested as indicators of vulnerability due to the danger of a single physical hazard impacting a large proportion of total population, and the prospect of relief or aid being far away, yet community cohesion often develops out of this same characteristic (Gaillard, 2007). Equally high exposure to physical environmental stressors over long periods of time clearly presents vulnerability, yet rich local knowledge can result from long histories of responding to these risks (Mercer et al, 2012;Walshe & Nunn, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, poverty is both cause and consequence of disasters in under-developed or developing countries. Disaster risk reduction is particularly essential for sustaining the achievements of all kinds of development goals since it provides a safety net for the hard-earned development gains of a developing country (Holloway 2003;Birkmann and von Teichman 2010;Walshe and Nunn 2012). In Nepal, it is a great challenge to protect infrastructure and public and individual properties from frequent landslide, flood, and earthquake disasters.…”
Section: Introductionmentioning
confidence: 99%